Learning barriers at the workplace: Development and validation of a measurement instrument - Anselmann, Sebastian (Frontiers in Education, 2022)
While facilitating factors to learning at the workplace have been well investigated, throughout the past decade less has emerged about the barriers that occur when approaching a learning activity at the workplace. Barriers to learning at the workplace are factors that hinder the initiation of successful learning, interrupt learning possibilities, delay proceedings or end learning activities much earlier than intended. The aim of this study is to develop and validate an instrument that measures barriers to informal and formal learning at the workplace. An interview pre-study asked 26 consultants about their learning barriers based on existing instruments. Using this data as groundwork, a novel measuring instrument of barriers to informal and formal learning was developed. The instrument is comprised of five factors with items on individual barriers, organizational/structural barriers, technical barriers, change and uncertainty. To validate the scales, a cross-sectional questionnaire with 112 consultancy employees and freelancers was conducted. The validation included exploratory factor analysis, internal consistency assessment, confirmatory factor analysis and convergent validity assessment. The results generated a three-factor scale barrier measurement for formal learning and a two-factor scale barrier measurement for informal learning. All scales featured Cronbach’s alpha values ranging between .80 and .86. With this developed and validated scales it is intended to help offer insights into factors that hinder individuals from learning at the workplace, and show organizations their potential for change.